Correlation of femoral version measurements between computed tomography and magnetic resonance imaging studies in patients presenting with a femoroacetabular impingement-related complaint. Issue 4 (27th July 2022) - Goldsmith, Campbell; Cheng, Jennifer; Mintz, Douglas; Moley, Peter
ABSTRACT: Computed tomography (CT) is considered the gold standard for femoral version measurement. However, recent data have shown magnetic resonance imaging (MRI) as another modality to measure femoral version. This study aimed to correlate MRI and CT femoral version measurements in patients presenting with a femoroacetabular impingement (FAI)-related complaint. Patients (18–35 years old) who presented to the hip preservation clinic and radiology department with a suspected FAI diagnosis from 26 December 2018 to 4 March 2020 were included. All patients had a CT and MRI of the hip, with images including both hips and knees, as per our institution's protocol for possible hip preservation surgery. Patients were excluded if they were missing views of the knees, or if they had a history or imaging appearance of any condition affecting femoral version at the femoral head (e.g. slipped capital femoral epiphysis). Femoral version was measured by three reviewers. Fifty-eight patients were included, and 36 (62%) were female. Femoral version averaged 6.1° ± 11.8° on CT and 6.5° ± 10.8° on MRI. A strong positive correlation was reported between the two imaging modalities ( r : 0.81; P < 0.001). Inter-rater reliability among the three reviewers was excellent and statistically significant for measurements on both MRI [intraclass correlation coefficient (ICC): 0.95; 95% CI: 0.85, 0.99; P < 0.001] and CT (ICC: 0.97; 95% CI: 0.92, 0.99; P < 0.001). Our finding suggests that MRI is a sufficient method for measuring femoral version to determine disease etiology and treatment progression. To avoid exposing patients to ionizing radiation, physicians should not obtain CT scans to evaluate femoral version.